Take it easy

Algebra Level 3

for any integer k>1000 A = n = 1 k ( 1 ) n ( n + 1 ) 2 n + n = 1 k + 1 ( 1 ) n ( n + 1 ) 2 n + n = 1 k + 2 ( 1 ) n ( n + 1 ) 2 n + n = 1 k + 3 ( 1 ) n ( n + 1 ) 2 n A= \large \displaystyle\sum_{n=1}^{k}(-1)^{\frac{n(n+1)}{2}}n + \large \displaystyle\sum_{n=1}^{k+1}(-1)^{\frac{n(n+1)}{2}}n + \large \displaystyle\sum_{n=1}^{k+2}(-1)^{\frac{n(n+1)}{2}}n + \large \displaystyle\sum_{n=1}^{k+3}(-1)^{\frac{n(n+1)}{2}}n if the sum of all possible values of A is m post your answer as 2m . note: don't combine the repeated values.


The answer is -8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Jafar Badour
Oct 29, 2015

if n ( m o d ( 4 ) ) = 0 o r ( n + 1 ) ( m o d ( 4 ) ) = 0 n(mod(4))=0 or (n+1)(mod(4))=0 then g ( n ) = n ( n + 1 ) 2 g(n)=\frac{n(n+1)}{2} is an even number this yields that H ( n ) = ( 1 ) g ( n ) = 1 H(n)=(-1)^{g(n)} =1 else means H ( n ) = 1 H(n) =-1 , its obvious that numbers are divisible by 4 take the sequence n=4,8,12,16,20...

so when n and n+1 are divisible by 4 that means the sequence is 4-1,4,8-1,8,12-1,12... meaning 3,4,7,8,11,12,...

when n takes the values above this means that g ( n ) g(n) is an even number which means H ( n ) = 1 H(n)=1

so when n takes 1 , 2, 3, 4, 5 ,6, 7, 8,9,10...

H(n) takes -1,-1,+1,+1,-1,-1,+1,+1,-1,-1...

I will simplify the equation

A = 4 i = 1 k + 3 f ( n + 1 ) + 2 f ( n + 2 ) + f ( n + 3 ) A=4\displaystyle \sum_{i=1}^k +3f(n+1)+2f(n+2)+f(n+3)

f ( n ) = ( 1 ) n ( n + 1 ) 2 f(n)=(-1)^{\frac{n(n+1)}{2}}

i = 1 k \displaystyle \sum_{i=1}^k while k>1000 then i = 1 k \displaystyle \sum_{i=1}^k is k ,0,-1,-k-1

if (k)(mod(4))=0 then i = 1 k = k \displaystyle \sum_{i=1}^k =k and

A = 4 k + 3 f ( n + 1 ) + 2 f ( n + 2 ) + f ( n + 3 ) A=4k+3f(n+1)+2f(n+2)+f(n+3)

A = 4 k 3 ( k + 1 ) 2 ( k + 2 ) + ( k + 3 ) = 4 A=4k-3(k+1)-2(k+2)+(k+3)=-4

if (k+1)(mod(4))=0 then i = 1 k = 0 \displaystyle \sum_{i=1}^k =0 and

A = 0 + 3 ( k + 1 ) 2 ( k + 2 ) ( k + 3 ) = 4 A=0+3(k+1)-2(k+2) -(k+3)=-4

if (k+2)(mod(4))=0 then i = 1 k = k 1 \displaystyle \sum_{i=1}^k =-k-1 and

A = 4 4 k 3 ( k + 1 ) + 2 ( k + 2 ) + ( k + 3 ) = 0 A=-4-4k-3(k+1)+2(k+2)+(k+3)=0

if (k)(mod(4))=1 then i = 1 k = 1 \displaystyle \sum_{i=1}^k =-1 and

A = 4 3 ( k + 1 ) + 2 ( k + 2 ) + ( k + 3 ) = 0 A=-4-3(k+1)+2(k+2)+(k+3)=0

the possible values are 0,-4 so m=-4 and 2m=-8!

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...